The Elusive Predictive Ability of Global Inflation1 . (7th June 2016) - Medel, Carlos A.; Pedersen, Michael; Pincheira, Pablo M.
Abstract: In this paper we analyse the utility of international measures of inflation in predicting local ones. To that end, we consider a set of 31 OECD economies for which monthly inflation data are available. Three main conclusions emerge. First, there is an important share of countries for which relatively robust evidence of predictability is found for both core and headline inflation. Second, the share of countries for which there is evidence of robust predictability is about the same for core and headline inflation, although gains in root‐mean‐squared prediction error are higher for headline inflation. Third, while the evidence indicates that an international inflation factor may be a useful predictor for several countries, it also indicates that, for many countries as well, predictability is either questionable, undetectable, non‐robust or simply non‐existent.